The cleansing hour [videorecording (DVD)] - LeVeck, Damien; LeVeck, Damien; LeVeck, Damien; Guzman, Ryan, 1987-; Gallner, Kyle; Angelis, Alix (Image Entertainment, 2020)
Two friends run a webcast which streams live exorcisms, but things take an unexpected turn when one of the actors becomes possessed by an actual demon and takes the crew hostage.